Erosion–corrosion behaviour of spark plasma sintered WC - 12Co in aggressive media. (August 2017) - Ige, O.O.; Aribo, S.; Obadele, B.A.; Langa, T.; Oluwasegun, K.M.; Shongwe, M.B.; Olubambi, P.A.
Abstract: Erosion-corrosion is a complex degradation mechanism prevalent in multiphase system and material selection is a strategy to mitigate the destructive process. This study evaluates the candidature of spark plasma sintered WC-12Co in aggressive media and with sand particles via rotating cylinder electrode. Corrosion and hardness tests were carried out, and the cermets surface morphology was examined. General corrosion results from total mass loss showed the least degradation resistance in sulphuric acid which informed the recommendation of the alloy for industrial applications in simulated mine water and seawater. Localised attack parameters from cyclic potentiodynamic polarization and the micrographs were well correlated. Graphical abstract: Highlights: Uniform and localised corrosion of spark plasma sintered WC-12Co in slurry environment were evaluated. The cermets are suitable for simulated mine water and seawater compared to sulphuric acid environment. Localised corrosion data correlates with the microstructure. Cermets hardness decreased as the cobalt binder dissolution increased.